Clinical evaluation of a novel multibolus contrast agent injection protocol for thoraco-abdominal CT angiography: Assessment of homogeneity of arterial contrast enhancement. Issue 126 (May 2020) - Obmann, Markus M.; Gehweiler, Julian; Schindera, Sebastian T.; Janetzki, Julia; Boll, Daniel T.; Benz, Matthias R.
Highlights: A multibolus injection for long-range CTA was established in patients. A multibolus injection provides a plateau of homogenous arterial enhancement. Arterial attenuation is more homogenous than in a single-bolus injection. In aortic dissections attenuation differences between lumina are reduced. Abstract: Purpose: To evaluate the in vivo feasibility of a multibolus contrast agent (CA) injection protocol with a reduced CA volume for thoraco-abdominal CT angiography (CTA) and to compare it to a single-bolus CA injection protocol. Method: 63 patients who underwent CTA with the multibolus protocol (60 ml CA) were divided in two groups either without (group 1, n = 48) or with (group 2, n = 15) aortic dissection. The aortic contrast enhancement was measured in group 1 using manual ROI analysis (10 segments), as well as semi-automated linear attenuation profiles. A subgroup (n = 18) of group 1, who also underwent imaging with the single-bolus protocol (94 ml CA), was used to compare both protocols. In group 2, differences in attenuation of the true and the false lumen for both the single- and the multibolus protocol were assessed with ROI attenuation measurements in both lumina. Comparisons were made using Wilcoxon test. Results: Average attenuation was above 200 HU for 98 % of cases using the multibolus protocol. There was superior contrast homogeneity for the multibolus protocol with a lower standard deviation of attenuation values along the length of the scan (p = 0.003), while average attenuation was higher for the single-bolus protocol (p = 0.002). Prolonged enhancement plateau lead to a more uniform opacification of the true and the false lumen in patients with aortic dissection using the multibolus protocol (p = 0.012). Conclusions: The multibolus protocol in thoraco-abdominal CTA is feasible in patients. It shows consistently high arterial enhancement with superior contrast homogeneity compared to a single-bolus protocol in patients with and without aortic dissection.